IMPLEMENTATION OF DIFFERENTIATED-BLENDED LEARNING USING CANVA MEDIA TO INCREASE LEARNING MOTIVATION OF MATHEMATICS SUBJECT IN CLASS VIII OF SMPI AL-MUNAWAR, TULUNGAGUNG REGENCY - Samsul Bakri (ARITMATIKA: Jurnal Riset Pendidikan Matematika, 2024)
The need for differentiated learning is very urgent because students have various abilities. Students' motivation also varies and needs to be improved. Therefore, learning motivation can be improved by implementing differentiated learning. This study is a field study with a mixed approach to exploratory models. Data collection techniques used in-depth interviews, participant observation, documentation studies and questionnaires. Data analysis used was qualitative analysis using the Miles, Huberman and Saldana models and the ANOVA test for quantitative analysis. The results of this study are: Educators at SMPI Al-Munawar implement differentiated learning as an implementation of an independent curriculum. In differentiated learning at SMPI Al-Munawar, it is carried out with modifications and innovations even though it is a method of modifying the method of combining several learning methods so that it is able to understand students and also modify learning media using Canva media so that it can reduce student boredom. Based on the results of the ANOVA test, it was stated that there was a significant interaction between the application of differentiated learning of materials, products and methods based on Canva on the motivation to learn mathematics at SMPI Al-Munawar.